Corporate social responsibility and capital budgeting - Martin, Patrick R. (Accounting, Organizations and Society, 2021)
Using an experiment, I examine whether managers have preferences for corporate social responsibility (CSR) in a capital budgeting setting and the factors that influence the extent to which they act on these preferences. I find that managers have and act on preferences for CSR by reporting to implement higher cost CSR investments that reduce firm profit even when they have financial incentives not to do so. I also find that when managers need to misreport to act on their preferences for CSR, their willingness to act on such preferences is decreased due to a desire to be honest. Conversely, an opportunity to create slack for personal benefit increases managers’ willingness to act on their CSR preferences, offsetting the decrease resulting from honesty concerns. Together these findings demonstrate that managers’ preferences for CSR investments can influence behavior even in the presence of competing economic incentives and social norms. Finally, an analysis of firm profit shows that firms may be better off financially with managers who act on preferences for CSR investments rather than managers who have strong preferences for wealth. This result obtains because managers with strong CSR preferences do not create slack to the same extent as managers with strong preferences for wealth. These results have implications for both theory and practice because they show that managers’ reports used to make investment decisions are influenced by their personal CSR preferences.